Martín Chambi in black and white - Colán, Mario (2006)
Martín Chambi J. (Coasa, 1876-1973) -photographer of Puno origin- has been the subject of innumerable publications and exhibitions throughout our recent history. His work has been exhibited both in Lima, Arequipa, and in that stately Cusco that saw most of his production. Many historians, anthropologists and other researchers, from their respective fields, have spoken of it, leaving evidence of its incredible artistic and ethnographic value. However, it is in this book by Andrés Garay Albújar where the photographer speaks -as the title says- for himself.